Improving the performance of hospitals: An architectural analysis of patient journeys in China - Peng, Dejian (A+BE | Architecture and the Built Environment, 2022)
Nowadays, we are faced with serious challenges in public health worldwide. However, the challenges cannot be solved only in the domain of architecture, medical science or management. A successful hospital building is more than a nice building or an efficient healing machine. Patient journey is such a concept that tries to explore the possibility to solve the problems in hospitals in the domain of hospital architecture and hospital management. In this context, the research proposes a study of patient journey in hospitals from the perspective of architecture on basis of the outcomes achieved in management. Patient journeys are transferred from both clinical and administrative processes to special patterns. Moreover, in such a visual way, both the efficiency and effectiveness of hospitals and patients’ satisfaction during the journeys in hospitals are analyzed with case studies of China and the Netherlands. The system of spatialized patient journeys helps architects and hospital managers broaden their understanding of hospital. And the comparison results from case studies are useful for hospitals in China to improve performance and patients’ satisfaction.